Retrospective evaluation of “Rods and Rings” pattern detected in the anti-nuclear antibody (ANA) indirect immunofluorescence (IIF) test - İnal, Neşe; Kurumanastırlı, Berke; Taşkınoğlu, Tutku; Duran, Alev Çetin; Togay, Alper; Sarıgüzel, Fatma Mutlu; Kaşifoğlu, Nilgün; Soylu, Mehmet; Doğan, Yavuz; Us, Ebru; Sarıbaş, Zeynep; Kaklıkkaya, Neşe; et al. (Frontiers in Immunology, 2024)
Anti-rods and rings (anti-RR) antibodies have recently been described as a cytoplasmic pattern in IIF-based screening of autoantibodies on HEp-2 cells and ICAP has named it as AC-23. It is most frequently related to drug-induced antibody generation. This study aimed to investigate the clinical significance of AC-23 positivity and its relevance to the diagnosis and/or follow-up of the associated diseases and/or drug use. A multicenter retrospective study was conducted among 10 hospitals from six different provinces in Türkiye from January 2017 to December 2021. The laboratory data and clinical information of 600 patients with positive anti-RR antibodies out of 547.558 HEp-2 IIF ANA samples were analyzed. The distribution of AC-23 positive patients by year indicated a steady increase between 2017-2021. Anti-RR prevalence in post-COVID-19 period was significantly higher than that of pre-COVID-19 period (p=0.00). Concomitant ANA positivity was detected in 56.5% of patients, the most common patterns being AC-4 and AC-5 (41.1%). The most frequent pathology among the anti-RR positive patients was an autoimmune disease (19.83%); 28.57% of which had rheumatoid arthritis and 17.65% autoimmune liver disease. Among the 600 patients, 65 (10.83%) were diagnosed as hepatitis C virus (HCV) infection. Available data for 38 of the HCV patients revealed that 71.05% of them had a history of interferon alfa+ribavirin and 28.95% of them had a history of NS3/4/5A/5B polymerase inhibitor or protease inhibitor drug use. Significant increase in the rate of anti-RR positivity was observed in the post-COVID-19 period when compared to pre-COVID-19 period (p:0.00). This is the first multicenter study in Türkiye about the clinical association of anti-RR antibodies which may be ignored during routine HEp-2 IIF testing. Pathologies other than HCV should be taken into consideration in terms of the possible role of anti-RR in autoimmune diseases and other pathologies. The preliminary data obtained in this study suggest that anti-RR antibody development might also be associated to COVID-19, supporting the several previous data related to the potential of viruses triggering the formation of autoantibodies. Large-scale prospective studies should elucidate the clinical significance of RR pattern and determine its role in patient diagnosis and follow-up.